THE RESTORATIVE JUSTICE PROCESS IN THE WAKE OF THE GLOBAL PANDEMIC - Nagore PÉREZ HIERRO (Challenges of the Knowledge Society)
The COVID-19 pandemic has completely changed the way we relate, both personally and socially, and at work. Isolation, confinement, restrictions or fear of contagion have led to the need to adapt to a virtual reality. And so, although many sectors have been paralyzed, many others are experiencing an express maturation thanks to the phenomenon of the Internet. In the field of justice, it has also been proposed to implement the judicial processes in a telematic way. However, the Spanish system is not yet ready to face virtual reality. Spain is suffering a significant collapse in the courts, due to the unprecedented health crisis. It is therefore necessary to promote alternative processes of conflict resolution, embodied in restorative justice, as an expeditious and effective way out of this saturation of the judicial system. To this end, it is vital to have sufficient regulatory support to regulate such reparation processes, such as criminal mediation, which lacks systematic regulation in our legal system, as well as to enable online sessions in order for us to embrace the new virtual reality defined after the pandemic.